Enlightenment and the creation of German Catholicism - Printy, Michael O'Neill (Cambridge Univ. Press, 2009)
Introduction -- Perfect societies : rethinking the church and the state -- The liberty of the German church : febronianism and the German Gallicans -- The German church and the absolute state -- Church and empire in the eighteenth century -- Collegialism : the rise of the state and the redefinition of the church -- The universal church and the universal class -- Catholic enlightenment and the search for a bourgeois Catholicism -- A program for reform -- Pastors of enlightenment : reforming the secular clergy -- Gallican longings : nation and religion in the German enlightenment -- Conclusion